Atmospheric mercury at an urban station in Korea across three decades. (April 2016) - Kim, Ki-Hyun; Brown, Richard J.C.; Kwon, Eilhann; Kim, Ik-Soo; Sohn, Jong-Ryeul
Abstract: The concentrations of total gaseous mercury (TGM) over three decades (1987–2013) were monitored at an urban station at Yan San (YS), Seoul, Korea. The results were examined by considering the prominent patterns in observed concentrations during periods where data were available: [1] period I (P1) = Sep. 1987 to Oct. 1988, [2] period II (P2) = Sep. 1999 to Jul. 2000, [3] period III (P3) = Jan. 2004 to Dec. 2011, and [4] period IV (P4) = Jan. 2012 to Dec. 2013. The data in this study indicate that the concentrations of TGM decreased abruptly from P1 (∼15 ng m −3 ) to P2 (∼5 ng m −3 ). Then, during the most of P3 ( i.e., from 2004 to 2011), the annual mean values were nearly constant and their concentrations were in the range 3–4 ng m −3 . The mean values then decreased to ∼2 ng m −3 in P4. Hg levels in the late 1980s reflect the dominant role of major man-made source processes ( e.g., unabated combustion of much dirtier fossil fuels). Unlike the earlier Hg monitoring data, the concentrations of Hg in recent periods could be attributed to a shift from coal to kerosene and natural gas in urban areas and to more stringent emissions regulations and cleaner fuels. It is unclear currently whether the latest and lowest concentrations measured during in P4 will be maintained during upcoming years, although they seem to reflect the direct impact of air quality control efforts since the 1980s. Highlights: Long-term trends of Hg are affected in reply to inputs affecting its sources/sinks. Emissions-concentration relationship of Hg has been reduced by control efforts. We assessed how much further Hg can be reduced or it is in steady-state equilibrium.